2022
DOI: 10.3389/fphys.2021.809419
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Sensitivity Decreased Significantly in Patients With Insulin Resistance Undergoing in vitro Fertilization and Embryo Transfer

Abstract: Ovarian sensitivity could affect the outcome of in vitro fertilization and embryo transfer (IVF-ET). The objective of this study was to explore the relationship between the ovarian sensitivity index (OSI) and traditional ovarian response makers and observe the relationship between OSI and insulin resistance (IR). The patients enrolled in this study included 131 patients with polycystic ovary syndrome (PCOS) with IR (PCOS-IR), 52 patients with PCOS without IR (PCOS-N), 164 patients with control with IR (control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
1
7
1
Order By: Relevance
“…Few studies have been performed on the association between HOMA-IR and OSI. To our knowledge, only one research depicted a decreased OSI in 131 IR-PCOS women compared with 52 non-IR PCOS subjects ( 11 ). However, the sample size was small and the effect size of IR on OSI was unclear.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Few studies have been performed on the association between HOMA-IR and OSI. To our knowledge, only one research depicted a decreased OSI in 131 IR-PCOS women compared with 52 non-IR PCOS subjects ( 11 ). However, the sample size was small and the effect size of IR on OSI was unclear.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the identification of heterogenous ovarian sensitivity in PCOS populations is the key to striking a balance between ovarian hyperstimulation syndrome (OHSS) and poor ovarian response (POR). Some clinical parameters, including age, body mass index (BMI), anti-mullerian hormone (AMH), and antral follicle count (AFC) have been widely used as predictive markers of ovarian response ( 11 ). However, these markers cannot properly reflect the dynamic process of follicular growth in response to exogenous gonadotropin (Gn) ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“… 36 Previously, in a case–control study, Zheng et al reported that a limited number of PCOS patients with IR had lower OSI levels than that of PCOS individuals without IR undergoing ART. 24 However, they found no statistical difference in OSI levels between the IR and non-IR groups in non-PCOS patients which was probably due to the small sample size. In our cohort study, the inverse relationship between HOMA-IR and OSI remained significant in all subgroups after careful adjustments, including the stratifications of age, BMI, COH protocol PCOS and other main infertility factors.…”
Section: Discussionmentioning
confidence: 91%
“… 23 Ovarian sensitivity index (OSI) has been suggested as an evaluation of ovarian sensitivity in IVF procedure, which could reflect the potential of follicles to produce oocytes in response to exogenous Gn stimulation. 24 , 25 The OSI improves the definition of ovarian response patterns. For instance, among young women, OSI showed a log-normal distribution with levels for poor and high response at 1.697 and 10.07, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance has previously been shown to have a negative correlation with ovarian sensitivity [ 37 ]. Metformin has been the most commonly-studied insulin sensitizer in PCOS patients.…”
Section: Ivf Preparationmentioning
confidence: 99%